Optimization of FIR Filter Parameters using TLBO Algorithm - Pandey, Ranjan Raj; Bhattarai, Deepa (Journal of Science and Technology, 2024)
This paper introduces an approach for optimizing low pass FIR filter parameters using the Teaching-Learning Based Optimization (TLBO) algorithm. The optimization focuses on minimizing error between the desired and actual response. Performance of designed FIR digital filter have been compared with the performance of Particle Swarm Optimization (PSO). Optimization of same order and the MATLAB simulation have confirmed the superiority of the proposed design in terms of smaller pass band and stop band ripples.